Effect of Eucommia ulmoides Leaf Extract on Growth Performance, Carcass Traits, Parameters of Oxidative Stress, and Lipid Metabolism in Broiler Chickens - Yan, Jiahao; Hu, Ruizhi; Li, Baizhen; Tan, Jijun; Wang, Ying; Tang, Zhiyi; Liu, Ming; Fu, Chenxing; He, Jianhua; Wu, Xiaosong (Frontiers in Veterinary Science, 2022)
Eucommia ulmoides bark has been traditionally used as a Chinese medicine to attenuate stress, but the leaf, which is rich in polyphenols and polysaccharides, has been rarely used. This study aimed to investigate the effect of Eucommia ulmoides leaf extracts (EULE) on oxidative stress and meat quality of broilers. A total of 252 broilers were randomly divided into 3 treatments, and fed with a control basal diet (CON), or a diet containing 250 mg/kg or 1000 mg/kg of EULE for 51d. Results showed that dietary supplementation of 250 mg/kg EULE increased significantly the average daily gain of broilers in the early stage (1-21 d), while 250 mg/kg or 1000 mg/kg of EULE decreased the feed conversion ratio in the whole period (P < 0.05). Supplementation of 250 mg/kg EULE reduced the level of MDA in liver (P<0.05), while 1000 mg/kg EULE decreased serum level of MDA (P<0.05), and the HDL level in serum was increased by 250mg/kg or 1000mg/kg EULE (P< 0.05). Additionally, 250 mg/kg EULE decreased abdominal fat ratio and serum triglyceride level in broilers, while 250 mg/kg or 1000 mg/kg of EULE reduced drip loss in breast muscle (P < 0.05), and 1000 mg/kg EULE reduced the cooking loss in thigh muscle (P < 0.05). In conclusion, dietary supplementation of 250 mg/kg of Eucommia ulmoides leaf extract could attenuate oxidative stress, and improve the growth performance and meat quality in broilers.